Association of an inherited genetic variant with vincristine-related peripheral neuropathy in children with acute lymphoblastic leukemia - Diouf, Barthelemy (JAMA, 2015)
IMPORTANCE: With cure rates of childhood acute lymphoblastic leukemia (ALL) exceeding 85%, there is compelling need to mitigate treatment toxicities that can compromise quality of life. Peripheral neuropathy is the major dose-limiting toxicity of the microtubule inhibitor vincristine, an anticancer agent given to every child with ALL. OBJECTIVE: Identify genetic germline variants associated with the occurrence or severity of vincristine-induced peripheral neuropathy in children with ALL. DESIGN, SETTING AND PARTICIPANTS: All patients had been enrolled in one of two prospective clinical trials for childhood ALL that included treatment with 36–39 doses of vincristine. Genome-wide single nucleotide polymorphism (SNP) analysis and vincristine-induced peripheral neuropathy were assessed in all patients from whom DNA was available (n=321 patients); 222 patients (median age at 6.0 years, range 0.1–18.8 years) enrolled between 1994–1998 on the St. Jude Children’s Research Hospital protocol Total XIIIB (St. Jude cohort) with toxicity followed through January 2001, and 99 patients (median age 11.4 years, range 3.0–23.8 years) enrolled between 2007–2010 on the Children’s Oncology Group protocol AALL0433 (COG cohort) with toxicity followed through May 2011. Human leukemia cells and induced pluripotent stem cell neurons were used to assess the effects of lower CEP72 expression on vincristine sensitivity. EXPOSURES: Treatment with vincristine at a dosage of 1.5 or 2.0 mg/m(2) as a component of protocol directed chemotherapy for childhood ALL. MAIN OUTCOMES AND MEASURES: Vincristine-induced peripheral neuropathy was assessed at each clinic visit using the National Cancer Institute Common Terminology Criteria for Adverse Events and prospectively graded as mild (grade 1), moderate (grade 2), serious/disabling (grade 3), or life-threatening (grade 4). RESULTS: Grade 2–4 vincristine-induced neuropathy during continuation therapy occurred in 28.8% of patients (n=64 of 222) in the St. Jude cohort and in 22.2% of patients (n=22 of 99) in the COG cohort. A SNP in the promoter region of the CEP72 gene, which encodes a centrosomal protein involved in microtubule formation, had a significant association with vincristine neuropathy (meta p =6.3 × 10(−9)). This SNP had a minor allele frequency of 37% (235/642), with 50 of 321 patients (16%, 95% CI 11.6%–19.5%) homozygous for the risk allele (TT at rs924607). Among patients with the high-risk CEP72 genotype (TT at rs924607), 28 of 50 patients (56%, 95% CI 41.2–70.0) developed at least one episode of grade 2–4 neuropathy, a higher rate than in patients with the CEP72 CC or CT genotype (58 of 271 patients; 21.4%, 95% CI 16.9–26.7); p=2.4×10(−6). The severity (grade) of neuropathy was greater (2.4-fold by Poisson regression (p<0.0001), 2.7-fold based on mean grade of neuropathy (1.23 [95% CI 0.74 – 1.72] versus 0.45 [95% CI 0.3 – 0.6]; t test p=0.004)) in patients homozygous for the CEP72 risk allele (TT genotype), compared to patients with the CC or CT genotype. The CEP72 promoter SNP was shown to create a binding site for a transcriptional repressor causing lower mRNA expression, and reducing CEP72 expression in human neurons and leukemia cells increased their sensitivity to vincristine. CONCLUSIONS: In this preliminary study of children with ALL, an inherited polymorphism in the promoter region of CEP72 was associated with increased risk and severity of vincristine-related peripheral neuropathy. If replicated in additional populations, this finding may provide a basis for safer dosing of this widely prescribed anticancer agent.